Human pathogens in plant biofilms: Formation, physiology, and detection. Issue 7 (25th January 2017) - Ximenes, Eduardo; Hoagland, Lori; Ku, Seockmo; Li, Xuan; Ladisch, Michael
ABSTRACT: Fresh produce, viewed as an essential part of a healthy life style is usually consumed in the form of raw or minimally processed fruits and vegetables, and is a potentially important source of food‐borne human pathogenic bacteria and viruses. These are passed on to the consumer since the bacteria can form biofilms or otherwise populate plant tissues, thereby using plants as vectors to infect animal hosts. The life cycle of the bacteria in plants differs from those in animals or humans and results in altered physiochemical and biological properties (e.g., physiology, immunity, native microflora, physical barriers, mobility, and temperature). Mechanisms by which healthy plants may become contaminated by microorganisms, develop biofilms, and then pass on their pathogenic burden to people are explored in the context of hollow fiber microfiltration by which plant‐derived microorganisms may be recovered and rapidly concentrated to facilitate study of their properties. Enzymes, when added to macerated plant tissues, hydrolyze or alter macromolecules that would otherwise foul hollow‐fiber microfiltration membranes. Hence, microfiltration may be used to quickly increase the concentration of microorganisms to detectable levels. This review discusses microbial colonization of vegetables, formation and properties of biofilms, and how hollow fiber microfiltration may be used to concentrate microbial targets to detectable levels. The use of added enzymes helps to disintegrate biofilms and minimize hollow fiber membrane fouling, thereby providing a new tool for more time effectively elucidating mechanisms by which biofilms develop and plant tissue becomes contaminated with human pathogens. Biotechnol. Bioeng. 2017;114: 1403–1418. © 2017 Wiley Periodicals, Inc. Abstract : Microbial cultivation and enrichment combined with plating and/or PCR, often used to detect foodborne pathogens, is a time consuming approach that may limit the number of variables to be tested and consequently the data generated. Replacement or reduction of time for culture methods by liquid microfiltration using hollow fibers accelerates time for foodborne pathogen detection.